Menguatkan identitas pancasila dalam demokrasi oleh gen z - Renata, Ririn (Maliki Interdisciplinary Journal, 2025)
Pancasila as the foundation of the Indonesian continues to face challenges in the modern era, especially amidst the dynamics of democracy and globalization that influence the younger generation, including Gen Z. Role of Gen Z in democracy is becoming increasingly important in the digital era influenced by technological advances. They can improve fairness and integrity in the election process by actively participating in election supervision. In Indonesia, the participation of young people is very important to support democratic participation and strengthen the values of Pancasila as the state ideology and morals. The results of the syudy show that Gen Z has uniqueness in internalizing Pancasila values. They tend to use technology to express their views on justice, unity, and diversity that are in line with Pancasila values. Gen Z has an important role in strengthening democracy in Indonesia, especially through their active involvement in elections, social campaigns, and political movements. This paper aims to examine how Gen Z can apply the values of Pancasila in everyday life and in their active participation in the democratic process and explore how they can strengthen the ethics and democratic system in Indonesia.